UN peacekeeping in civil wars - Howard, Lise Morje (Cambridge : Cambridge University Press, 2008)
Civil wars pose some of the most difficult problems in the world today and the United Nations is the organization generally called upon to bring and sustain peace. Lise Morj Howard studies the sources of success and failure in UN peacekeeping. Her in-depth analysis of some of the most complex UN peacekeeping missions debunks the conventional wisdom that they habitually fail, showing that the UN record actually includes a number of important, though understudied, success stories. Using systematic comparative analysis, Howard argues that ...
1. Introduction; 2. The failures: Somalia, Rwanda, Angola, Bosnia; 3. Namibia the first major success; 4. El Salvador: centrally-propelled learning; 5. Cambodia: organizational dysfunction, partial learning and mixed success; 6. Mozambique: learning to create consent; 7. Eastern Slavonia: institution-building and the limited use of force; 8. East Timor: the UN as state; 9. The ongoing multidimensional operations; 10. Conclusion: two levels of organizational learning.
Civil wars pose some of the most difficult problems in the world today and the United Nations is the organization generally called upon to bring and sustain peace. Lise Morj Howard studies the sources of success and failure in UN peacekeeping. Her in-depth analysis of some of the most complex UN peacekeeping missions debunks the conventional wisdom that they habitually fail, showing that the UN record actually includes a number of important, though understudied, success stories. Using systematic comparative analysis, Howard argues that ...
Keywords: United Nations -- Peacekeeping forces; Intervention (International law); Civil war -- Protection of civilians